2010
DOI: 10.1073/pnas.1007276107
|View full text |Cite
|
Sign up to set email alerts
|

A Trojan horse mechanism of bacterial pathogenesis against nematodes

Abstract: Understanding the mechanisms of host-pathogen interaction can provide crucial information for successfully manipulating their relationships. Because of its genetic background and practical advantages over vertebrate model systems, the nematode Caenorhabditis elegans model has become an attractive host for studying microbial pathogenesis. Here we report a "Trojan horse" mechanism of bacterial pathogenesis against nematodes. We show that the bacterium Bacillus nematocida B16 lures nematodes by emitting potent vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
127
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(136 citation statements)
references
References 43 publications
6
127
0
3
Order By: Relevance
“…The results reported here shed light on one such strategy-release of toxic aromatic compounds by the hydrolysis of b-glucosides by members of Enterobacteriaceae. In contrast to the antipredatory actions of pathogenic bacteria that have evolved specific tools such as extracellular proteases targeted against predators [21], our studies involved non-pathogenic bacteria that are armed only with genes that enable the uptake and hydrolysis of aromatic b-glucosides. The energy investment is minimal for the bacterium and a part of it could be derived from the glucose generated during the hydrolysis of b-glucosides.…”
Section: Discussionmentioning
confidence: 99%
“…The results reported here shed light on one such strategy-release of toxic aromatic compounds by the hydrolysis of b-glucosides by members of Enterobacteriaceae. In contrast to the antipredatory actions of pathogenic bacteria that have evolved specific tools such as extracellular proteases targeted against predators [21], our studies involved non-pathogenic bacteria that are armed only with genes that enable the uptake and hydrolysis of aromatic b-glucosides. The energy investment is minimal for the bacterium and a part of it could be derived from the glucose generated during the hydrolysis of b-glucosides.…”
Section: Discussionmentioning
confidence: 99%
“…All these compounds are known attractants for C. elegans (Matsumori et al, 1989;Bargmann et al, 1993;Niu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Bristol strain N2 was cultured on semi-liquid oat medium (10 g of oats, 6 ml of distilled water) at 28°C for 6 to 8 days. The cultured nematodes were grown to adulthood separated using the Baerman funnel technique, and distilled water suspension of the nematode was prepared as a working stock (Niu et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Binary assays have 56 also shown that C. elegans learns to avoid pathogenic bacteria, if the worms are exposed to the 57 pathogen prior to a binary choice feeding behaviour experiment (Zhang, Lu & Bargmann, 2005). 58Worms may be attracted to certain diffusible odorants and repelled by others (Bargmann, 59 Hartwieg & Horvitz, 1993; Schulenburg & Ewbank, 2007), however, Bacillus nematocida both 60 attracts and kills C. elegans, thereby acting as a nematode predator (Niu et al, 2010). C. elegans 61 feeding behaviour, sensing and decision making regarding food sources is complex and involves 62 multiple neural pathways (Schulenburg & Ewbank, 2007; Sengupta, 2013 Escherichia coli OP50 was used as a non-pathogenic food source for cultivating C. elegans.…”
mentioning
confidence: 99%